2004
DOI: 10.1002/mds.20056
|View full text |Cite
|
Sign up to set email alerts
|

Most effective stimulation site in subthalamic deep brain stimulation for Parkinson's disease

Abstract: The optimal stimulation site in subthalamic deep brain stimulation (STN-DBS) was evaluated by correlation of the stereotactic position of the stimulation electrode with the electrophysiologically specified dorsal STN border. In a series of 25 electrodes, best clinical results with least energy consumption were found in contacts located in the dorsolateral border zone, whereas contacts within the subthalamic white matter, e.g., zona incerta, were significantly less effective. We suggest that the dorsolateral ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
150
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(166 citation statements)
references
References 21 publications
14
150
0
2
Order By: Relevance
“…While our patient-specific model system suffers from a number of limitations, the comparisons with our clinical measurements are consistent with previous studies on location of therapeutically effective electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). The results of this study, though limited to a single patient, suggest that the therapeutic volume of tissue to activate is centered on ZI/H2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While our patient-specific model system suffers from a number of limitations, the comparisons with our clinical measurements are consistent with previous studies on location of therapeutically effective electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). The results of this study, though limited to a single patient, suggest that the therapeutic volume of tissue to activate is centered on ZI/H2 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…These studies have resulted in general guidelines on the selection of stimulation parameters, as well as clinical algorithms for programming the devices. Imaging studies have developed correlations between stimulation parameters and markers of brain activity (Hershey et al, 2003;Haslinger et al, 2005;Phillips et al, 2006;Trost et al, 2006), and identified the location of therapeutic DBS electrode contacts (Saint-Cyr et al, 2002;Voges and J, 2002;Herzog et al, 2004;Zonenshayn et al, 2004;Kitagawa et al, 2005;Nowinski et al, 2005;Plaha et al, 2006). Modeling studies have characterized the theoretical effects of DBS electric fields on the underlying neural tissue (McIntyre et al, 2004b;Miocinovic et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the improvements in motor function, several clinical trails have yielded information about negative limbic effects of STN DBS, including depression, apathy, and decreased cognitive function [7,8] . Recent studies, however, have reported that the most effective contact of a quadripolar DBS lead (contact 3 in DBS of the STN) lies dorsal/dorsomedial to the STN, in the region of the zona incerta (ZI) [9][10][11] . The ZI, an embryological derivate of the ventral thalamus, is a small horizontally elongated area of grey matter cells in the subthalamic region of the mesencephalon.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Herzog et al [30] demonstrated that the effective DBS contacts located in the dorsolateral STN border produced the best clinical results. Neurosurgeons at our institution also regard the dorsolateral portion of the STN as the most favorable stimulation site in STN DBS.…”
Section: Targeting Techniquesmentioning
confidence: 99%